Radiofrequency Ablation of Persistent Atrial Fibrillation: Diagnosis-to-Ablation Time, Markers of Pathways of Atrial Remodeling, and Outcomes. (January 2016) - Hussein, Ayman A.; Saliba, Walid I.; Barakat, Amr; Bassiouny, Mohammed; Chamsi-Pasha, Mohammed; Al-Bawardy, Rasha; Hakim, Ali; Tarakji, Khaldoun; Baranowski, Bryan; Cantillon, Daniel; Dresing, Thomas; Tchou, Patrick; et al.
Abstract : Background—: Various ablation strategies of persistent atrial fibrillation (PersAF) have had disappointing outcomes, despite concerted clinical and research efforts, which could reflect progressive atrial fibrillation–related atrial remodeling. Methods and Results—: Two-year outcomes were assessed in 1241 consecutive patients undergoing first-time ablation of PersAF (2005–2012). The time intervals between the first diagnosis of PersAF and the ablation procedures were determined. Patients had echocardiograms and measures of B-type natriuretic peptide and C-reactive protein before the procedures. The median diagnosis-to-ablation time was 3 years (25th–75th percentiles 1–6.5). With longer diagnosis-to-ablation time (based on quartiles), there was a significant increase in recurrence rates in addition to an increase in B-type natriuretic peptide levels ( P =0.01), C-reactive protein levels ( P <0.0001), and left atrial size ( P =0.03). The arrhythmia recurrence rates over 2 years were 33.6%, 52.6%, 57.1%, and 54.6% in the first, second, third, and fourth quartiles, respectively ( P categorical <0.0001). In Cox Proportional Hazard analyses, B-type natriuretic peptide levels, C-reactive protein levels, and left atrial size were associated with arrhythmia recurrence. The diagnosis-to-ablation time had the strongest association with the ablation outcomes which persisted in multivariable Cox analyzes (hazard ratio for recurrence per +1Log diagnosis-to-ablation time 1.27, 95% confidence interval 1.14–1.43; P <0.0001; hazard ratio fourth versus first quartile 2.44, 95% confidence interval 1.68–3.65; P categorical <0.0001). Conclusions—: In patients with PersAF undergoing ablation, the time interval between the first diagnosis of PersAF and the catheter ablation procedure had a strong association with the ablation outcomes, such as shorter diagnosis-to-ablation times were associated with better outcomes and in direct association with markers of atrial remodeling.